Influence of stretch and pressure as mechanical stresses on skeletal muscle - Noriteru Morita; Shingo Takada; Koichi Okita (Japanese Society of Physical Fitness and Sports Medicine, 2013)
Mechanical forces induced by skeletal muscle contraction generate intramuscular stresses as well as external tension. Skeletal muscle cells can sense and adapt to mechanical stresses to maintain cellular homeostasis. Compared to the effects of hormone and growth factors (e.g., insulin, insulin-like growth factor, and other cytokines) on physiological and biochemical properties in skeletal muscle, the implications and molecular mechanisms concerning responses of skeletal muscle to mechanical stresses are still largely unclear. In this short review, we focus on the influences of mechanical stresses, especially intramuscular pressure and stretching, on the contraction of skeletal muscles, and review current results from studies examining the effects of mechanical stresses.